Environmental Impact Assessment of Kathmandu Terai Fast-Track - Dahal, Padam Kanta; Dahal, Lalita; Khanal, Sarina; Poudel, Sazina; Khatiwada, Bhawana (International Journal of Environment, 2014)
Road transport is dominant necessity for the overall economic development of any nation. In case of Nepal, an easy access between the Capital City and Terai, the store-house of the country and is very necessary. To facilitate this promotion of an improved core road network, Government of Nepal has launched the Kathmandu Terai Fast Track Project. Many concerned personalities and sectors had considered this project to be number one in the list of seventeen projects of national pride declared by the government. The main objective of this study was to identify the impacts of proposed project implementation on physical, biological, socio-economic and cultural environment of the project area and propose mitigation measures to avoid or mitigate such impacts. Primary information collection and secondary data review was the source of data with cross sectional descriptive study design. Data was taken purposively in the project affected area. Length of 72.6 km fast track from Kathmandu – Lalitpur – Makawanpur and up to Nijgadh in Bara district to link with the East West Highway will be of four lanes with 50 m on each side. The project was proposed to have 96 bridges big or small; 1.6 km long tunnel will be built in Thingan of Makawanpur on public-private partnership. It had projected costs of more than NRs 250 million. The impacts on land use will be on about 30km of agricultural land, 43km of forests and about 3km of other land uses, bridges etc. in the main alignment. The impacts on human life will mainly be in villages near the alignment. There are 38 villages within about 50m of the main alignment. The project can be continued with minimum of environmental degradation by applying the mitigation measures. Nation has been investing a lot of resources. Upon the completion of the fast track, the distance and time to reach the capital city from Terai will come down to only 1.5 hours and will transform the capital, eastern Terai and the country as a whole. It is estimated that NRs 4.5 billion will be saved annually of the transport cost. Therefore, Kathmandu Terai Fast Track Project can be considered as the single most important prospect for the improvement of traffic conditions and the creation of a major economic impact in Nepal over the coming decade. DOI: http://dx.doi.org/10.3126/ije.v3i4.11726 International Journal of Environment Vol. 3, No. 4, 2014 Page: 1-11